Updates on synthesis and biological activities of 1, 3, 4-oxadiazole: A review. Issue 20 (18th October 2017) - Salahuddin,; Mazumder, A.; Yar, M. Shahar; Mazumder, R.; Chakraborthy, G. S.; Ahsan, Mohamed Jawed; Rahman, Mujeeb Ur
ABSTRACT: The new era of heterocyclic moieties which are developed in the decades plays a very important role in the treatment of various diseases. Among them are 1, 3, 4-oxadiazoles, a heterocyclic five-membered ring which plays an vital role in the development of newer medicinal compounds for treating various biological activities, such as proliferation of cells, tuberculosis, allergy, viral diseases, etc. The present review will summarize the various synthetic approaches which will be correlated with the biological activities so that the information in future may be used by many researches to give a path breaking lead in the field of medicinal chemistry. GRAPHICAL ABSTRACT: